Redressing the Past: A Critical Legal Assessment of """"quota"""" allocations in post-apartheid South Africa under the Marine Living Resources Act 18 of 1998 in the hake deep-sea trawl and West Coast rock lobster near-shore sectors - Daniels, Gregory (Institute of Marine and Environmental Law, 2014)
The South African government faces numerous challenges in redistributing resources and ensuring access to those resources by historically disadvantaged individuals. This is particularly relevant in the fishing industry where people have been dependant on marine living resources, but under Apartheid, were restricted from accessing these resources. The manner and extent to which the South African government seeks to address the injustices of the past in fisheries allocations is an important indication of its commitment to transformation. Transformation of the fishing industry must be balanced against the South African government's commitment to promote historically disadvantaged individuals on the one hand, and sustainable development, the internal transformation of previously advantaged companies and the government's commitment under international human rights and environmental law instruments on the other. The South African government's Department of Environmental Affairs and Tourism has published numerous White Papers and laws that recognise the government's role as custodian of natural resources and the need for the redistribution of resources especially to historically disadvantaged individuals. However, the manner in which legislation and policy is implemented and, more importantly, the way transformation is interpreted by the courts is an important indication of what levels of transformation would satisfy the courts that transformation was considered and given effect to. As stated above, this is important not only for the fishing industry sector but for the redistribution and transformation processes in other areas as well. Transformation requires a marked change. The process under the Marine Living Resources Act and the levels of transformation that it has achieved resembles a negotiated settlement, where the process in allocating fishing rights is relatively transparent, rather than change that is so significant that it may be considered as marked.